Diffusion of information among small-scale farmers in Senegal: the concept of Farmer Field Schools - Diemuth E. Pemsl; Hermann Waibel; Rudolf Witt (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Recent research on the Farmer Field School (FFS) approach in agriculture in developing countries has raised some doubts on the economic impacts of this concept and especially the knowledge diffusion effects from trained to non-trained farmers. Based on a study in Senegal this paper hypothesizes that the question of the project placement strategy is vital when analyzing knowledge diffusion effects of FFS in Africa. Results show that the share of trained farmers in a community is a decisive factor for adoption behavior and knowledge diffusion. It is concluded that when introducing an FFS, a critical mass of trained farmers is important to attain effective dissemination of information and to generate positive stimuli for adoption and learning among non-participants.
Keywords: 330; Africa; Senegal; agricultural extension; Farmer Field School; diffusion